Impact of quarterly professional-mode flash glucose monitoring in adults with type 2 diabetes in general practice (GP-OSMOTIC): Secondary psychological and self-care outcomes of a pragmatic, open-label, 12-month, randomised controlled trial. (September 2021) - Speight, Jane; Holmes-Truscott, E.; Thuraisingam, Sharmala; Mohamad Husin, Hanafi; Manski-Nankervis, Jo-Anne; De La Rue, Katie; Ginnivan, Louise; Audehm, Ralph; Clark, Malcolm; Khunti, Kamlesh; O'Neal, David; Furler, John; et al.
Abstract: Aims: To investigate the impact of quarterly professional-mode flash glucose monitoring on psychological outcomes in adults with type 2 diabetes in primary care. Methods: The GP-OSMOTIC trial randomised 299 adults with type 2 diabetes in 25 general practices to quarterly use of professional-mode flash glucose monitoring (sensor worn for 14 days; data discussed at clinic visit) or usual care. At baseline and 12 months, participants completed validated measures: general emotional well-being (WHO-5), diabetes-specific quality of life (DIDP), satisfaction with glucose monitoring (GME-Q), self-care activities (SDSCA) and perceived involvement in clinical care (PICS). Linear mixed-effects models examined between-group differences at 12 months. Results: At 12 months, there were no clinically important between-arm differences in any secondary psychological or self-care outcomes. Per protocol analyses showed no clinically significant between-group differences. Conclusions: The GP-OSMOTIC intervention had no significant impact, at 12 months, on general emotional well-being, diabetes-specific quality of life or satisfaction with glucose monitoring, suggesting no added psychological burden. Lack of positive impact on self-reported self-care activities or perceived involvement in clinical care may warrant closer attention to the fidelity of intervention delivery, the context (e.g. the nature of clinician-patient interactions) and/or the sensitivity of the measures, as these will help plan future studies.